Perceived of indoor environmental quality in missionary school / Siti Nurqamarina Zarqa Zakaria and Intan Bayani Zakaria - Zakaria, Siti Nurqamarina Zarqa; Zakaria, Intan Bayani (2018)
Indoor Environmental Quality (IEQ) is defined as a quality of building's environment in relation to health and wellbeing of those who occupy space within it such as in the office, library and school building. The quality of the interior building environment of the school is important because based on previous studies the IEQ can affect the performance, comfort and health of the students. The age of the building also plays important criteria in contributing a good IEQ in a building. In Malaysia, missionary school building that is more than 100 years still play their rules serving as a primary and secondary school. As a starting point for knowledge dissemination, schools need to provide a conducive environment to produce excellent students. The aim of this study is to determine the student's perception of indoor environmental quality at three (3) missionary in Perak that consists of four (4) main criteria. The result of the study shows that overall students were satisfied with the comfort level and lighting system in their schools. The schools need an improvement of privacy and noise level in order to increase the overall satisfaction of students in the school. Lastly, the results also show that there are 3 major health problems towards students which are stress, itch and dry skin.